2004
DOI: 10.1007/s00253-004-1735-y
|View full text |Cite
|
Sign up to set email alerts
|

Klebsiella planticola strain DSZ mineralizes simazine: physiological adaptations involved in the process

Abstract: We examined the ability of a soil bacterium, Klebsiella planticola strain DSZ, to degrade the herbicide simazine (SZ). Strain DSZ is metabolically diverse and grows on a wide range of s-triazine and aromatic compounds. DSZ cells grown in liquid medium with SZ (in 10 mM ethanol) as carbon source mineralized 71.6+/-1.3% of 0.025 mM SZ with a yield of 4.6+/-0.3 microg cell dry weight mmol(-1) carbon. The metabolites produced by DSZ during SZ degradation included ammeline, cyanuric acid, N-formylurea and urea. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Taken together, these experiments are consistent with the conclusion that cyanuric acid metabolism proceeds through allophanate exclusively in all the strains tested. This is important to establish because almost all papers discussing s-triazine ring degradation over the last 20 years have presumed that urea is the pathway intermediate in all bacteria isolated for their ability to mineralize melamine, ammeline, and s-triazine herbicides (1,6,12,30,34,36). The hydrolysis of biuret at the subterminal carbon-nitrogen bond is chemically plausible, so it is certainly possible that some bacteria might hydrolyze biuret to yield urea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, these experiments are consistent with the conclusion that cyanuric acid metabolism proceeds through allophanate exclusively in all the strains tested. This is important to establish because almost all papers discussing s-triazine ring degradation over the last 20 years have presumed that urea is the pathway intermediate in all bacteria isolated for their ability to mineralize melamine, ammeline, and s-triazine herbicides (1,6,12,30,34,36). The hydrolysis of biuret at the subterminal carbon-nitrogen bond is chemically plausible, so it is certainly possible that some bacteria might hydrolyze biuret to yield urea.…”
Section: Discussionmentioning
confidence: 99%
“…In subsequent years, the cyanuric acid pathway shown in Fig. 1 (upper pathway) has been attributed to other bacteria that grow on melamine or s-triazine herbicides (12,30,34,36).…”
mentioning
confidence: 99%
“…A study by Balangué et al [53] with E. coli HB101 strain demonstrated that the toxicity of 2,4-D could reduce the fluidity of bacterial membrane, and consequently alter MDA results, as a system-wide response against ROS. Sánchez et al [56] also reported similar findings, where the strain Klebsiella planticola DSZ, when in contact with ethanol or the herbicide simazine, exhibited a decrease in the saturation of membrane lipids, altering the rate of selective permeability, possibly as a defense system.…”
Section: Resultsmentioning
confidence: 64%
“…The activity of microorganisms which modifies herbicides activity can proceed various ways which hence lead either to decreasing or increasing their toxicity. Microorganisms can use herbicides as food or energy source or exploit the product of herbicides degradation as biosynthesis of humic acids precursors (Gebendinger and Radosevich 1999; Sánchez et al 2005). …”
Section: Introductionmentioning
confidence: 99%
“…Biotechnological methods allow to recreate natural environment conditions, and they are less expensive and quite often easier as well as more effective (Sánchez et al 2005). As with petroleum derivatives, there is the possibility of biological utilization of hazardous pesticides on half-technical scale.…”
Section: Introductionmentioning
confidence: 99%